Socio‐demographic, behavioural and health‐related characteristics associated with active commuting in a regional Australian state: Evidence from the 2016 Tasmanian Population Health Survey. (18th October 2020) - Stanesby, Oliver; Long, Michael; Ball, Kylie; Blizzard, Leigh; Cocker, Fiona; Greaves, Stephen; Harpur, Siobhan; Johnston, Fay; Jose, Kim; Marshall, Elaine; Palmer, Andrew J.; Sharman, Melanie; et al.
Abstract: Issue addressed: Physical activity is lower and rates of preventable common diseases are higher in regional/rural than urban Australia. Active commuting (walking/bicycling to get from one place to another) may benefit health through increased physical activity, but most evidence of its correlates come from urban studies. This study aimed to investigate associations between active commuting, socio‐demographic characteristics, behaviours, total physical activity and health in a regional/rural Australian state. Methods: This study used data from the 2016 Tasmanian Population Health Survey, a representative cross‐sectional self‐report survey of 6, 300 adults in Tasmania, Australia. Logistic regression modelling investigated associations between socio‐demographic, behavioural and health characteristics and past week active commuting frequency. Results: In multivariable models, being younger, having tertiary qualifications, living in a socio‐economically advantaged area, being physically active, having a healthy body mass index and good/excellent self‐rated health were associated with engaging in more active commuting. Inner regional dwellers were no more likely than outer regional dwellers to actively commute after covariate adjustment. Conclusion: Strategies to promote active commuting in regional/rural areas might consider targeting older adults, those less educated, those living in socio‐economically disadvantaged areas, those less physically active, those with poorer health and those with higher body mass index. Research could further investigate why these groups appear to be less active for commuting purposes. So what?: Increasing physical activity and active commuting may help to reduce rates of preventable common diseases in regional/remote areas.